Measurement of syneretic properties of rennet-induced curds and impact of factors such as concentration of milk: A review. (September 2019) - Panthi, Ram R.; Kelly, Alan L.; O'Callaghan, Donal J.; Sheehan, Jeremiah J.
Abstract: Background: The rate or extent of whey expulsion or syneresis from cheese curds during stirring in-vat determines curd moisture levels, which subsequently influences cheese moisture content. The outward migration of whey depends on curd contraction and on the structure of the pores permitting whey movement. Curd syneretic properties are one of the least understood areas of cheese science, particularly when milk of varying composition is used. Scope and approach: This review provides an insight into the mechanisms of curd formation and curd syneresis, and factors influencing syneretic properties in unconcentrated and concentrated milk and appraises syneresis measurement methods in terms of their relative strengths and weaknesses. Key findings and conclusions: Direct measurement of moisture content of curds is recommended as a simple and reliable method for measurement of syneresis of industrial relevance and, although inline measurement for curd moisture prediction has been a significant development in the last decade, its application to commercial production is still limited. A review of previous studies found that experimental conditions and methodologies used to measure syneresis vary widely, making it difficult to compare data between studies. Overall, interactions between process variables employed determines whether syneresis is accentuated or inhibited, and this can be exploited by cheese producers to attain target curd moisture contents by varying process parameters, particularly when milk is concentrated prior to cheese-making. Furthermore, further studies should be focused on endogenous syneresis and casein network rearrangement to clearly elucidate this mechanism and its influence on macrosyneresis under dynamic conditions. Highlights: Determining curd moisture content is a reliable technique for measurement of syneresis kinetics. Modelling for prediction of inline curd moisture content is of growing interest. The pattern of syneresis from protein-concentrated milk is complex. Endogenous syneresis under dynamic conditions requires greater understanding. Future studies should focus on interactive effects between variables.